Morphological and biochemical indicators of blood of rats poisoned by carbon tetrachloride and subject to action of liposomal preparation - Gutyj, B.; Martyshchuk, T.; Bushueva, I. V.; Semeniv, B.; Parchenko, V. V.; Kaplaushenko, A. H.; Magrelo, N.; Hirkovyy, A.; Musiy, L.; Murska, S.; Бушуєва, Інна Володимирівна; Парченко, Володимир Володимирович; et al. (My University, 2017)
The article gives the results of the research on the influence of a developed complex liposomal preparation on the dynamics of morphological and biochemical indicators of the blood of rats subjected to modeled oxidative stress caused by intermuscular injection of 50% carbon tetrachloride at a dose of 0.25 ml per 100 g of body mass. We found that in conditions of intoxication by carbon tetrachloride, the physiological level of hematological indicators of the researched animals’ body was disrupted. This is indicated by the reduction in the amount of erythrocytes, hemoglobin content, concentration of hemoglobin per erythrocyte, increase in the amount of leucocytes, mass of hemoglobin per erythrocyte and increase of colour indicator. Also, we detected suppression of protein synthesis function of the liver. The levels of total protein and albumin fraction were below the normal physiological level. High indicators were observed in the levels of creatinine, urea and total bilirubin. In order to normalize the functional state of the liver under oxidative stress it is reasonable to use a liposomal preparation which contains butafosfan, interferon, thistle and vitamins. In order to normalize morphological and biochemical indicators of the blood of rats subject to intoxication of carbon tetrachloride it is reasonable to use a liposomal preparation that contains butafosfan, selenium, thistle, methionine and vitamins. Using the liposomal preparation Butaselmevit for rats under oxidative stress the morphological and biochemical indicators in the blood normalized. On the 14th day the indictors of the number of erythrocytes, the hemoglobin content, the white blood cell count and red blood indexes compared to control came within the physiological indicators, indicating a recovery of hematopoietic function of the bone marrow and normalized indicators of the functional state of the liver.
Keywords: carbon tetrachloride; liver; Butaselmevit; butafosfan; selenium; milk thistle; vitamins; methionine